Transparency report disclosure by Australian audit firms and opportunities for research. Issue 8 (5th October 2015) - Fu, Yi; Carson, Elizabeth; Simnett, Roger
Abstract : Purpose: – The purpose of this study is to compare the information disclosed by leading Australian audit firms in their first-time audit firm transparency reports. Australia has mandated the preparation and release of transparency reports by audit firms in 2013 to provide better information to stakeholders about audit firms, their governance and their internal governance systems. These reports promote increased transparency regarding issues which are believed to contribute to audit quality. Design/methodology/approach: – The paper takes the form of an archival analysis where the authors summarise the governance and other information for the 21 leading Australian audit firms as disclosed in their first-time 2013 transparency reports. Findings: – The authors find that audit firms meet the minimum transparency report disclosure requirements, but have different approaches to governance in the areas which may impact audit quality. These areas include: the internal quality control systems, independence practices, continuing education and partners' remuneration structures. The authors identify specific areas where transparency reports may give rise to future research opportunities. Originality/value: – Australia is one of the first countries to require audit firms to publish transparency reports, and this is the first study to examine these reports. By summarising transparency report disclosures, we present a comprehensive picture of how Australian leading audit firms govern and oversee their business activities. This is useful to transparency report preparers, report users and regulators.